Crosstalk Between Innate and T Cell Adaptive Immunity With(in) the Muscle - Bonomo, Adriana C.; Pinto-Mariz, Fernanda; Riederer, Ingo; Benjamim, Claudia F.; Butler-Browne, Gillian; Mouly, Vincent; Savino, Wilson (Frontiers in Physiology, 2020)
Growing evidence demonstrates a continuous interaction between the immune system and the skeletal muscle in inflammatory diseases of different pathogenetic origins, in dystrophic conditions such as Duchenne Muscular Dystrophy as well as during normal muscle regeneration. Although one component of the innate immunity, the macrophage, has been extensively studied both in disease conditions and during cell or gene therapy strategies aiming at restoring muscular functions, much less is known about dendritic cells and their primary immunological targets, the T lymphocytes. This review, although discussing the role of macrophages, will be focused on the dendritic cells and T lymphocytes (including effector and regulatory T-cells), emphasizing the potential cross talk between these cell types and their influence on the structure and function of skeletal muscle.